A new fibrin sealant as a three-dimensional scaffold candidate for mesenchymal stem cells - Gasparotto, Vinicius P. O. [UNESP]; Landim-Alvarenga, Fernanda C. [UNESP]; Oliveira, Alexandre L. R. [UNESP]; Simoes, Gustavo Ferreira; Lima-Neto, Joao F. [UNESP]; Barraviera, Benedito [UNESP]; Ferreira, Rui S. [UNESP] (Biomed Central Ltd., 2014)
Introduction: The optimization of an organic scaffold for specific types of applications and cells is vital to successful tissue engineering. In this study, we investigated the effects of a new fibrin sealant derived from snake venom as a scaffold for mesenchymal stem cells, to demonstrate the ability of cells to affect and detect the biological microenvironment.Methods: The characterization of CD34, CD44 and CD90 expression on mesenchymal stem cells was performed by flow cytometry. In vitro growth and cell viability were evaluated by light and electron microscopy. Differentiation into osteogenic, adipogenic and chondrogenic lineages was induced.Results: The fibrin sealant did not affect cell adhesion, proliferation or differentiation and allowed the adherence and growth of mesenchymal stem cells on its surface. Hoechst 33342 and propidium iodide staining demonstrated the viability of mesenchymal stem cells in contact with the fibrin sealant and the ability of the biomaterial to maintain cell survival.Conclusions: The new fibrin sealant is a three-dimensional scaffolding candidate that is capable of maintaining cell survival without interfering with differentiation, and might also be useful in drug delivery. Fibrin sealant has a low production cost, does not transmit infectious diseases from human blood and has properties of a suitable scaffold for stem cells because it permits the preparation of differentiated scaffolds that are suitable for every need.